Diminished oligomerization in the synthesis of new anti‐angiogenic cyclic peptide using solution instead of solid‐phase cyclization. Issue 3 (May 2016) - Rubio, Sandra; Clarhaut, Jonathan; Péraudeau, Elodie; Vincenzi, Marian; Soum, Claire; Rossi, Filomena; Guillon, Jean; Papot, Sébastien; Ronga, Luisa
ABSTRACT: The design and synthesis of novel peptides that inhibit angiogenesis is an important area for anti‐angiogenic drug development. Cyclic and small peptides present several advantages for therapeutic application, including stability, solubility, increased bio‐availability and lack of immune response in the host cell. We describe here the synthesis and biological evaluations of a new cyclic peptide analog of CBO‐P11: cyclo(RIKPHE), designated herein as CBO‐P23M, a hexamer peptide encompassing residues 82 to 86 of VEGF which are involved in the interaction with VEGF receptor‐2. CBO‐P23M was prepared using in solution cyclization, therefore reducing the peptide cyclodimerization occurred during solid‐phase cyclization. The cyclic dimer of CBO‐P23M, which was obtained as the main side product during synthesis of the corresponding monomer, was also isolated and investigated. Both peptides markedly reduce VEGF‐A‐induced phosphorylation of VEGFR‐2 and Erk1/2. Moreover, they exhibit anti‐angiogenic activity in an in vitro morphogenesis study. Therefore CBO‐P23M and CBO‐P23M dimer appear as attractive candidates for the development of novel angiogenesis inhibitors for the treatment of cancer and other angiogenesis‐related diseases. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 368–375, 2016.